UPAYA PENCEGAHAN DAN PENANGGULANGAN HIV/AIDS MELALUI PENINGKATAN PENGETAHUAN DAN SCREENING HIV/AIDS PADA KELOMPOK WANITA BERESIKO DI BELAWAN SUMATERA UTARA - Nur Afi Darti; Fatwa Imelda (Jurnal Riset Hesti Medan, 2019)
AIDS stands for Acquired Immune Deficiency Syndrome, a collection of symptoms and infections or commonly called syndromes caused by damage to the human immune system due to the HIV virus, while HIV stands for Human Immunodeficiency Virus, a virus that can weaken immunity in humans. The increasing rate of transmission of HIV/AIDS sexually, especially through sex, has replaced the position of transmission through needles in injecting drug users, as the main route of transmission of HIV. Increased rates of transmission through heterosexual groups have led to increasingly susceptible transmission to low risk groups such as housewives and infants. The HIV/AIDS case is an iceberg phenomenon that must immediately require special attention from health workers. Therefore this community service takes a precautionary and remedial approach with increasing knowledge, with health education and counseling before screening HIV / AIDS with a blood examination, the effort is to cut the chain of transmission of HIV/AIDS. And can be used as a basis for follow-up in treatment with anti retroviral (Anti Retroviral) for participants who are detected positive for HIV/AIDS. This community service was carried out in the Belawan region of  North Sumatra with 80 female participants examined and from the results of the examination there were no detectable women who were HIV/AIDS positive and there was an increase in knowledge about HIV AIDS regarding definitions, signs and symptoms, modes of transmission and methods prevention. So that it is expected that this increase in knowledge will reduce and avoid risky behavior.Keywords: knowledge, screening, HIV/AIDS